Interesting viscosity changes in the aqueous urea-ionic liquid system: effect of alkyl chain length attached to the cationic ring of an ionic liquid - Nanda, Raju; Rai, Gitanjali; Kumar, Anil (Journal of Solution Chemistry, 2015)
In the present article, we demonstrate the effect of urea on the structure of the ionic liquids in their aqueous solutions through viscometric methods. We unravel the structure altering effect of urea in its aqueous solutions of ionic liquids possessing higher alkyl chains. The finding is an attempt to discern the anomalous behavior of urea as shown in the past with the help of many techniques. Interestingly, in the aqueous solutions of the imidazolium based ionic liquids having substitution of -C4H9 and -C6H13 groups on the imidazolium ring, urea exhibits kosmotropic behavior. Further increase in the substituted alkyl group such as -C8H17 alters the urea behavior to be chaotropic.
Keywords: Alkyl chain length; ionic liquids; Structure-breaker; Structure-maker; Urea; viscosity